TO STUDY AND ANALYSIS OF PEM FUEL CELL WITH VARIOUS TYPE OF PARAMETERS - Mahobia, S.K. (International Journal of Engineering Technologies and Management Research, 2017)
In this paper, we are observed the PEM fuel Cells, which are consist of anode plate, cathode plate, separator, oxygen gases, and hydrogen gases. Separators are used to between the anode plate and cathode plate. The various mass flow rates of oxygen gases and hydrogen gases are obtaining with the help of controlling valve of cylinders. In this way we are achieving the various voltages.